Long-term dynamics of density dependence reveals a more stable effect of the neighborhood on tree growth than tree survival. - Liping Wang; Junjie Wu; Fengxian Chen (PLoS ONE)
Density dependence is a vital mechanism for explaining tree species diversity. Empirical studies worldwide have demonstrated that neighbor density influences plant survival and growth in various communities. However, it remains unclear how neighbor density affects plant survival and growth over extended periods. We used data from tree censuses collected every five years from 1981 to 2015 (seven intervals) to assess how density dependence affects adult tree survival and growth by using generalized linear mixed models and the coefficients of variation in Barro Colorado Island plot. Linear regression models were used to assess whether the effects of density dependence on tree survival and growth correlated with species abundance. The results indicated that the effects of tree size (DBH) on tree survival and growth differed across all intervals. We found that the effects of heterospecific neighbor density on tree survival varied over time and consistently had significant negative impacts on tree growth. Conspecific neighbor densities had significant negative effects on tree survival and growth across all intervals. The effect of density dependence on tree growth was more stable than its impact on tree survival. Additionally, the relationship of species abundance and the effect of negative conspecific and heterospecific neighbor densities significantly affected tree growth but not survival, with negative and positive correlations to tree abundance over time, respectively. Our results revealed that neighboring density dependence can predict more accurately of tree growth than survival.